A afetividade nas práticas pedagógicas: atitudes e expressões verbais nas interações professora- crianças, sob a perspectiva de Henri Wallon - Galiani, Simone da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research project presents starts with an investigation realized into the presence and also the characteristics of affectivity in the pedagogical practice of a child education’s teacher. The research`s process began linked with the research way of the Post-Graduate Education at UNESP – university located in Presidente Prudente, SP, called Childhood and Education and it adopted as the object of study the affectivity in early childhood education in the walloniana’s perspective of theory, in order to reflect about into the established pedagogical relations in the construction process of the interactions by children that are between 4 and 5 years old. Several studies, revealed that the affectivity (emotions, feelings and passions) is present in the educational context so it requires the actual presence of adults in child development. The research was based on a qualitative approach, using the case’s study, where the participants were a teacher and also twenty-two child students in an institution of a municipal school in Presidente Prudente-SP. It was used as techniques for gathering data, the classroom observations and a semi-structured interview with the teacher having in mind to know her concepts about affectivity and also her presence in the classroom. The observations that were done between the months of April and June of 2012 through interaction activities that the pedagogical practice used by the teacher summed up in two aspects that are present in the affective dimension: attitudes and verbal expressions. About the first one, it became clear that although the affection is constantly present in all moments of interaction in the educational environment, it still needs to be worked so to build meaningful interactions by children that is sometimes presented as something positive (dialogue, respect, care), and other times it was revealed as the shallowness in teacher-child relationships...

O presente trabalho de pesquisa partiu da investigação sobre a presença e características da afetividade na prática pedagógica de uma professora de educação infantil. O processo de análise iniciou-se vinculado à linha de pesquisa do Programa de Pós- Graduação- Mestrado em Educação da UNESP- Campus de Presidente Prudente-SP, denominada “Infância e Educação” e adotou como objeto de estudo a afetividade na educação infantil sob a ótica da teoria walloniana, com o intuito de refletir sobre as relações de interação estabelecidas entre professora e crianças de 4 e 5 anos de idade. Diversos estudos e pesquisas com enfoque na teoria walloniana revelam que a afetividade (emoções, sentimentos e paixões) está presente no contexto educativo de modo que necessite da presença concreta dos adultos no desenvolvimento infantil. A pesquisa partiu de uma abordagem qualitativa, do tipo estudo de caso, em que os participantes foram uma professora e vinte e duas crianças integrantes de uma instituição da Rede Municipal de Ensino de Presidente Prudente-SP. Utilizou-se como técnicas de recolha de dados, as observações em sala de aula e a entrevista semiestruturada com a professora visando conhecer suas concepções sobre afetividade e a presença da mesma em sala de aula. As observações, ocorridas entre os meses de abril e junho do ano de 2012, revelaram, por meio de episódios de interação, que a atuação pedagógica da professora resumiu-se em dois aspectos presentes na dimensão afetiva: atitudes e expressões verbais...
Keywords: Wallon, Henri, 1879-1962; Educação; Afetividade; Educação - Estudo e ensino; Professores e alunos; Educação de crianças; Education